Real-time digital simulator for distributed systems. (May 2021) - Chen, Jinchao; Du, Chenglie; Han, Pengcheng; Du, Xiaoyan
Simulation has been widely adopted as a support tool for the validation and experimentation of distributed systems. It allows different devices and applications to be evaluated and analyzed without requiring the actual presence of those machines. Although the simulation plays an important role in investigating and evaluating the behaviors of devices, it results in a serious simulator building problem as the distributed systems become more and more complicated and dynamically data driven. Most of the existing simulators are designed and developed to target a specific type of application, lacking the capabilities to be a configurable and standardized tool for researchers. To solve the adaptability and reusability problems of simulators, this paper proposes a new approach to design and implement a configurable real-time digital simulator for hardware devices that are connected via data buses in distributed systems. First, the proposed simulator uses a logic automaton to simulate the activities of a real device, and generates the incentive data for tested equipment according to the predefined XML-based files. Then with a virtual bus, the simulator can receive, handle, and send data in various network environments, improving the flexibility and adaptability of a simulator design. Experimental results show that the proposed simulator has a high real-time performance, and can meet the increasing requirements of modern simulations of distributed systems.